Overtime work, job autonomy, and employees’ subjective well-being: Evidence from China - Yang, Shusheng; Chen, Lijuan; Bi, Xianjin (Frontiers in Public Health, 2023)
Introduction Chinese workers suffer more from overtime than in many countries. Excessive working hours can crowd out personal time and cause work-family imbalance, affecting workers’ subjective well-being. Meanwhile, self-determination theory suggests that higher job autonomy may improve the subjective well-being of employees. Methods Data came from the 2018 China Labor-force Dynamics Survey (CLDS 2018). The analysis sample consisted of 4,007 respondents. Their mean age was 40.71 (SD = 11.68), and 52.8% were males. This study adopted four measures of subjective well-being: happiness, life satisfaction, health status, and depression. Confirmation factor analysis was employed to extract the job autonomy factor. Multiple linear regression methods were applied to examine the relationship between overtime, job autonomy, and subjective well-being. Results Overtime hours showed weak association with lower happiness (β = −0.002, p < 0.01), life satisfaction (β = −0.002, p < 0.01), and health status (β = −0.002, p < 0.001). Job autonomy was positively related to happiness (β = 0.093, p < 0.01), life satisfaction (β = 0.083, p < 0.01). There was a significant negative correlation between involuntary overtime and subjective well-being. Involuntary overtime might decrease the level of happiness (β = −0.187, p < 0.001), life satisfaction (β = −0.221, p < 0.001), and health status (β = −0.129, p < 0.05) and increase the depressive symptoms (β = 1.157, p < 0.05). Conclusion While overtime had a minimal negative effect on individual subjective well-being, involuntary overtime significantly enlarged it. Improving individual’s job autonomy is beneficial for individual subjective well-being.